KECUKUPAN PSAK 18 TENTANG AKUNTANSI DANA PENSIUN DALAM MENGAKOMODASI KEBUTUHAN STANDAR AKUNTANSI INVESTASI TANAH DAN BANGUNAN - DWIRANDRA, A. A. N. B. (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 1 (2010), 2010)
Accounting has power to control organization and social activities through numbers stated on the financial report. One way to produce these magnificent numbers is through the match of accounting treatment with accounting standard. This article criticizes whether the need of accounting standard on property investment of the pension fund has sufficiently been accommodated by PSAK 18. This study is motivated by an expectation that PSAK 18 does not provide sufficient support on the matter, because firstly, management of pension fund does not use PSAK 18 as the only basis for financial reporting; secondly, pension fund transactions is unique and develop rapidly thus the existing standard is not sufficient. The result shows that PSAK 18 has not been able to sufficiently accommodate the need of accounting standard on property investment related to measurement concept and presentation of the following transactions (1) jointly acquired investment asset; (2) the appropriate and inappropriate investment according to investment direction; (3) differences in investment status; and (4) notes on financial report. It is recommended to revise PSAK 18 by adjusting sentences and adding clauses.
Keywords: PSAK, investment asset, pension fund accounting.